Is there equity of access to revascularisation in Wales by socioeconomic deprivation? - Lloyd Evans (International Journal of Population Data Science, 2019)
Background Long-standing evidence of inequity has been shown to exist in the management of patients with heart disease. The majority of UK studies during the last 20 years have concluded that patients living in the most deprived areas were disadvantaged by lower revascularisation rates, despite having a higher level of need.